Pediatric gallbladder torsion managed by laparoscopic cholecystectomy: a case report and scoping review - Sun, Yi; Fang, Zheng; Cao, Xu; Zhang, Ting; Liu, Xiaobo; Zhang, Jie; Xiong, Qianwei; Wu, Bin; Yan, Xiangming (Frontiers in Pediatrics, 2025)
Gallbladder torsion (GT), characterized by the axial rotation of the cystic duct and cystic artery, is a critical condition that predominantly affects elderly women and is infrequently observed in children. Chronic cholecystitis associated with incomplete GT is a particularly rare phenomenon. This article presents a pediatric case of chronic cholecystitis associated with incomplete GT. Ultrasonography and magnetic resonance cholangiopancreatography (MRCP) were utilized to confirm the diagnosis in the child. Laparoscopic cholecystectomy was successfully performed on the child, with no postoperative complications. For children with chronic cholecystitis associated with incomplete GT, clinical manifestations may improve. However, due to the presence of congenital anatomical abnormalities, children's symptoms may recur. Early laparoscopic cholecystectomy can prevent the acute onset of torsion and potential difficulties in diagnosis at later stages.